Umroo: a seamless digital smart Umrah tracker - Hisham-muddin, Fikri; Asmad, Elyas; Nordin, Azlin (Akademia Baru Publishing, 2025)
This study introduces Umroo, a mobile application developed using the Agile development methodology and constructed usingthe Flutter platform. The Umrooproject is designed to address the logistical issues involved in coordinating large groups of Umrah and Hajj pilgrims, including navigation and emergency response services-related issues. Using the Agile Software Development process model, the system incorporates features such as real-time geolocation tracking, emergency notification systems, and health alert systems. A previous survey indicated a high demand for real-time location tracking and emergency response features, which was used to inform the design of the Umroo system to be user-friendly and intuitive. To facilitate digital transformation and enhance the effectiveness of pilgrimage management, the friendly mobile app supported by Google Cloud services and PostgreSQL was conceptualized and developerto supplement existing infrastructure despite limitations brought about by sparseness of networks. The Umroo projectachieved 96.8% success rate during user acceptance testing. The Umroo app aims to improve the security and well-being of pilgrims, minimize miscommunication between stakeholders, including mutawwifs and travel firms, and improve general pilgrimage management.